Porous hydroxyapatite for artificial bone applications - Iis, Sopyan; Mel, Maizirwan; Singh, Ramesh; Khalid, Kamarul Ariffin (Elsevier, 2007)
Hydroxyapatite (HA) has been used clinically for many years. It has good biocompatibility in bone contact as its chemical composition is similar to that of bone material. Porous HA ceramics have found enormous use in biomedical applications including bone tissue regeneration, cell proliferation, and drug delivery. In bone tissue engineering it has been applied as filling material for bone defects and augmentation, artificial bone graft material, and prosthesis revision surgery. Its high surface area leads to excellent osteoconductivity and resorbability providing fast bone ingrowth. Porous HA can be produced by a number of methods including conversion of natural bones, ceramic foaming technique, polymeric sponge method, gel casting of foams, starch consolidation, microwave processing, slip casting, and electrophoretic deposition technique. Some of these methods have been combined to fabricate porous HA with improved properties. These combination methods have yielded some promising results. This paper discusses briefly fundamental aspects of porous HA for artificial bone applications as well as various techniques used to prepare porous HA. Some of our recent results on development ofmporous HA will be presented as well.